2004
DOI: 10.1253/circj.68.763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Distal Protection Device During Primary Stenting in Patients With Acute Anterior Myocardial Infarction

Abstract: arly restoration of blood flow in the infarct-related artery (IRA) with consequent restitution of myocardial perfusion is the aim of treatment of patients with acute myocardial infarction (AMI). [1][2][3][4][5] A strategy of routine stent implantation during percutaneous coronary intervention (PCI) in AMI patients is the most immediate and reliable method for recanalizing the occluded artery, but the limitations of this strategy include distal embolism and a lower incidence of thrombolysis in myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 34 publications
0
31
1
Order By: Relevance
“…Nakamura, et al suggested that a strategy of thrombectomy therapy alone before stent implantation cannot prevent embolism related to these materials and that PCI with a distal protection device should be considered to be the only prevention therapy for noreflow phenomenon by distal embolism. 18) However, the Enhanced Myocardial Efficacy and Recovery by Aspiration of Liberated Debris (EMERALD) trial suggested that distal embolic protection did not result in improved microvascular flow, greater reperfusion success, reduced infarct size, or enhanced event-free survival, 29) and the results of the Protection Devices in PCI Treatment of Myocardial Infarction for Salvage of Endangered Myocardium (PROMISE) study revealed no benefit of distal protection. 30) The results of the Randomized Evaluation of the Effect of Mechanical Reduction of Distal Embolization by ThrombusAspiration in Primary and Rescue Angioplasty (REMEDIA) trial and other studies indicate that reperfusion is improved after thrombectomy, but whether these results can be transformed into small infarcts or better outcomes has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura, et al suggested that a strategy of thrombectomy therapy alone before stent implantation cannot prevent embolism related to these materials and that PCI with a distal protection device should be considered to be the only prevention therapy for noreflow phenomenon by distal embolism. 18) However, the Enhanced Myocardial Efficacy and Recovery by Aspiration of Liberated Debris (EMERALD) trial suggested that distal embolic protection did not result in improved microvascular flow, greater reperfusion success, reduced infarct size, or enhanced event-free survival, 29) and the results of the Protection Devices in PCI Treatment of Myocardial Infarction for Salvage of Endangered Myocardium (PROMISE) study revealed no benefit of distal protection. 30) The results of the Randomized Evaluation of the Effect of Mechanical Reduction of Distal Embolization by ThrombusAspiration in Primary and Rescue Angioplasty (REMEDIA) trial and other studies indicate that reperfusion is improved after thrombectomy, but whether these results can be transformed into small infarcts or better outcomes has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al reported the benefit of distal protection during PCI for AMI patients. 25 Their subjects were any AMI patients within 24 h of the onset of AMI without any exclusion of lesion morphology. Further study is necessary to identify cases suitable for distal protection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another report demonstrated that distal protection during PCI effectively retrieved the embolic debris and preserved the index of microcirculatory resistance in patients with an acute anterior STEMI [14]. Embolic protection devices are designed to be able to retrieve atherothrombotic debris and prevent its distal embolisation, but their effect on clinical outcomes has not been established, except for saphenous vein bypass grafts [6,7,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%